White matter hyperintensities, executive function and global cognitive performance in vascular mild cognitive impairment - Sudo,Felipe Kenji (2013)
Vascular mild cognitive impairment (VaMCI) represents an early symptomatic stage of vascular cognitive impairment and might be associated to fronto-executive dysfunction.MethodsTwenty-six individuals (age: 73.11±7.90 years; 65.4% female; schooling: 9.84±3.61 years) were selected through neuropsychological assessment and neuroimaging. Clinical and neuroimaging data of VaMCI individuals (n=15) were compared to normal controls (NC, n=11) and correlated with Fazekas scale.ResultsVaMCI performed significantly worse than NC in Trail-Making Test (TMT) B, errors in TMT B, difference TMT B-A and Cambridge Cognitive Examination (CAMCOG) final scores. Correlations were found among scores in modified Fazekas scale and performances in TMT B (time to complete and errors), difference TMT B-A and CAMCOG total score.ConclusionExtension of white matter hyperintensities might be correlated to poorer global cognition and impairments in a set of fronto-executive functions, such as cognitive speed, set shifting and inhibitory control in VaMCI.